Ionic transport study of plasticized salicylic acid doped polymethylmethacrylate based electrolytes - Isa, M.I.N.; Arof, Abdul Kariem (2009)
In this work, the ionic transport of DBPIDMF plasticized salicylic acid doped PMMA based gel electrolyte has been studied. The samples were prepared using solution cast technique. The number density of mobile ions and mobility of mobile ions were obtained from calculations based on the Rice and Roth Model. The mobility of the ions is between 10-9 to 10-6cm2V-1s-1 and the number density of mobile ions is between 1020to 1023 em".